Effective Ways for Raising Children Fluent in Two Languages - Law, John; Castañeda, Guadalupe (CIEX JOURNAL, 2020)
Raising children with two parents who have two different native languages can be problematic. Both parents would love if their children could grow up to be fluent in both of their native languages as they believe their children will have an advantage and achieve success in their future. This conference will show ways to effectively promote bilingualism in bilingual family which will result in families growing together and having success as individually members of a family.